Taxonomic revisions within Embiotocidae (Teleostei, Perciformes) based on molecular phylogenetics - Longo, Gary C.; Bernardi, Giacomo; Lea, Robert N. (Zootaxa, 2018)
Embiotocidae, a unique family within the Perciformes that has evolved a complex viviparous natural history, has lacked full resolution and strong support in several interspecific relationships until recently. Here we propose three taxonomic revisions within embiotocid surfperches based on recent molecular phylogenetic analyses that robustly resolve all interspecific relationship in the Eastern Pacific species: Hypsurus caryi (Agassiz, 1853) resurrected to its original name Embiotoca caryi Agassiz, 1853, Rhacochilus vacca (Girard, 1855) shifted into the genus Phanerodon Girard, 1854, and Hyperprosopon anale Agassiz, 1861 separated into the available genus Hypocritichthys Gill, 1862. The proposed changes would leave three previously paraphyletic groups monophyletic (Embiotoca, Hyperprosopon, and Phanerodon) and would maintain the current number of genera at 13.